2017
DOI: 10.1002/ejsp.2213
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism, resources, and the perception of human motion

Abstract: Is perception of human motion affected by psychosocial resources? According to the Resources and Perception Model, perception is jointly affected by subjective threat and psychosocial resources that buffer threat. Two experiments tested whether social threat (i.e., ostracism) and psychosocial resources affect perception of human motion. Observers attempted to identify human movement in ambiguous point‐light displays after being ostracized or not ostracized. Additionally, trait resources (self‐esteem plus socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Particularly, convincing evidence for the effects of exclusion on the early, perceptual processes comes from studies utilizing the SDT (Bernstein et al ., ; Gorman et al ., ; see also Müller, Jusyte, Trzebiatowski, Hautzinger, & Schönenberg, ). This approach is illuminating, as the SDT allows disentangling of participants’ discrimination accuracy from their response styles and other similar biases.…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 96%
See 1 more Smart Citation
“…Particularly, convincing evidence for the effects of exclusion on the early, perceptual processes comes from studies utilizing the SDT (Bernstein et al ., ; Gorman et al ., ; see also Müller, Jusyte, Trzebiatowski, Hautzinger, & Schönenberg, ). This approach is illuminating, as the SDT allows disentangling of participants’ discrimination accuracy from their response styles and other similar biases.…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 96%
“…One recent study suggested that sources of exclusion may be more readily detected than sources of inclusion, as in a binocular rivalry task, participants reported detecting the face of a person who had excluded them for a longer period than the face of the person who had included them (Golubickis et al ., ). Another recent study reported that in two experiments, excluded participants were less accurate than included participants in detecting whether vague videos contained human motion or not, suggesting that exclusion might impair detection of social stimuli (Gorman, Harber, Shiffrar, & Quigley, ). This is interesting, as earlier studies suggest that exclusion improves social stimulus identification (Bernstein et al ., ), that is, a process after detection.…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
“…Therefore, those who have sufficient resources should perceive threatening things in a less distorted way. RPM is supported by an increasing number of studies (Gorman et al, 2016;Harber et al, 2008Harber et al, , 2011Huynh et al, 2014;Schnall et al, 2008). RPM itself draws heavily on Proffitt's economy of action, Hobfoll's Conservation of Resources theory of resources and coping (Hobfoll, 1989), and classic and revised New Look theory (Easterbrook, 1959;Erdelyi, 1974;Greenwald, 1992).…”
Section: Absence Of Theorymentioning
confidence: 99%
“…Next, we explore the roles of psychosocial resources, extraversion and self-esteem, which influence how observers perceive biological movement and faces 62 64 . Individuals with high extraversion scores engage in more motor synchrony during conversation 65 and use representational gestures more frequently 66 , suggesting greater relevance of embodiment in everyday interactions.…”
Section: Introductionmentioning
confidence: 99%